ETIKA INFORMASI DALAM PERSPEKTIF AL-QUR’AN - Dapit Amril (Alfuad: Jurnal Sosial Keagamaan, 2017)
Events that occur in the Western hemisphere in seconds or minutes after that can be witnessed in the bedroom of people who are on the Eastern hemisphere continent. Likewise, events occurring in the Eastern hemisphere can be seen today by people in the Western Hemisphere. Indeed, societies’ lives can not be separated from rumors; this is caused by the existence of three types of people: First are the people who use the issue to damage the life of Islamic society, they are from the hypocrites and non-Muslims. The second is a person who easily receives the news and immediately conveys it to others without checking the truth. And the third is a person who easily mistake or quickly concluded then he immediately preach to others based on the false assumptions. The subject of this research is what and how the real description in the interpretation of the verses of the Qur'an about the information with analyzes the subject matter to give a certain concept of information. The discussion is based on the references to verses of the Qur'an and Hadiths that deal with the issues discussed. The purpose of this study is as follows; First, to know clearly about the ethics that provide the information so that the information submitted does not confuse the readers, listeners and viewers. Second, is to know clearly about ethics in receiving information in order to give guarantee of justice, balance and accuracy of the information.